Aid allocation, composition and effects - Clist, Paul (2010)
The thesis examines aid. It has two specific topics within that: the link between aid and domestic tax revenue, and aid allocation. In the chapter on aid and tax, it is shown that there is a negative link between aid in the form of grants and domestic tax revenue, but that this link is only found to be negative in the very earliest years of the sample (1970-1985). In more recent times, aid (grants or loans) have a positive effect on domestic tax revenue. There are two specific contributions within aid allocation. First, the reasons why aid is given are examined, and catalogued using the 4P framework: poverty, policy, population and proximity. Individual donors are examined, which allows a greater degree of clarity. Second, I move beyond examining the total amount of aid given, to study the type of aid given. It is shown that donors do practice policy selectivity at this level of disaggregation.